Infiltration of Inflammatory Cells in the Ovary Following Oral Administration of Monosodium Glutamate - Ilegbedion, IG; Onyije, FM; Chibuike, OO (Bangladesh Journal of Medical Science, 2013)
Background: Monosodium glutamate (MSG) a sodium salt of naturally occurring (non-essential) L-form of glutamic acid is one of the main flavor enhancer used as an ingredient in various food products. It is widely used in restaurants, packaged food industries and household kitchens, in Nigeria, most communities and individuals often use MSG as a bleaching agent for the removal of stains from clothes. Materials and Methods: Twenty (20) female adult wistar rats were used for this experiment. The rats with average weight of 181g were randomly assigned into four groups of five each (Groups A, B, C and D). Group A, B and C served as treatments groups while group D as the control. Each rat in the treatment groups A, B and C received 0.1g/kg, 0.15g/kg and 0.20g/kg of monosodium glutamate respectively in 0.5ml of water orally three times daily for two weeks. Result: The histopathological evaluation of the tissues of the ovary showed Infiltration of inflammatory cells in and around the oocyte as well as in the zonal granulosa layer. There was distortion of tissue architecture. Conclusion: MSG alters the histology of the ovary, therefore its consumption should be stopped and to work out safe level of consumption further in depth studies are recommended. DOI: http://dx.doi.org/10.3329/bjms.v12i4.14235 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 413-418